Gabapentin Inhibits Protein Kinase C Epsilon Translocation in Cultured Sensory Neurons with Additive Effects When Coapplied with Paracetamol (Acetaminophen) - Vittorio Vellani; Chiara Giacomoni (The Scientific World Journal)
Gabapentin is a well-established anticonvulsant drug which is also effective for the treatment of neuropathic pain. Although the exact mechanism leading to relief of allodynia and hyperalgesia caused by neuropathy is not known, the blocking effect of gabapentin on voltage-dependent calcium channels has been proposed to be involved. In order to further evaluate its analgesic mechanisms, we tested the efficacy of gabapentin on protein kinase C epsilon (PKCε) translocation in cultured peripheral neurons isolated from rat dorsal root ganglia (DRGs). We found that gabapentin significantly reduced PKCε translocation induced by the pronociceptive peptides bradykinin and prokineticin 2, involved in both inflammatory and chronic pain. We recently showed that paracetamol (acetaminophen), a very commonly used analgesic drug, also produces inhibition of PKCε. We tested the effect of the combined use of paracetamol and gabapentin, and we found that the inhibition of translocation adds up. Our study provides a novel mechanism of action for gabapentin in sensory neurons and suggests a mechanism of action for the combined use of paracetamol and gabapentin, which has recently been shown to be effective, with a cumulative behavior, in the control of postoperative pain in human patients.